Panti Asuhan Anak Terlantar Di Pekanbaru Dengan Pendekatan Arsitektur Perilaku - Herlika Herlika; Pedia Aldy; Ratna Amanati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Nowadays, there are still children who have not been able to have the human right in social reality. One of the solution to handle this homeless children’s problem is throught an orphanage.An orphanage of homeless children is a social welfare agencies that has a role in improving the physical, mental, social and economic of homeless children condition. To fulfill this role, thebehavior architecture approach is applied to accommodate and empower the behavior of homeless children. Behavior aspects that applied are territory, privacy, personal space especiallyin dormitory that has privacy activities by using partition, wall and glass. Cluster territory at orphanage region is close region by one way of in and out. The concept of this design is thelabyrinth, which is based on the behavior of homeless children. The labyrinth has a meaning centered with open space in the center of the region, protect is applied with clusters, complex with explorative shape, and flow with arrange every space. In addition, connection spaces are considered based on behavior of homeless children at mosque, education building, clinic, home stay, dining room, gardening area, raising area and the field with arrange proximity space in every functions.Keywords: Orphanage, Homeless Children, Behavior Architecture, labyrinth.